Waardenburgs Syndrome (Type 1) in A Newborn of Consanguineous Parents: A Case Report - Naher, Sharifun; Das, Animesh Chandra (Bangladesh Journal of Child Health, 2015)
Abstract not available DOI: http://dx.doi.org/10.3329/bjch.v38i3.22825 Bangladesh J Child Health 2014; VOL 38 (3) :157-160